A Novel Nanocomposite with Superior Antibacterial Activity: A Silver‐Based Metal Organic Framework Embellished with Graphene Oxide. Issue 11 (3rd April 2018) - Firouzjaei, Mostafa Dadashi; Shamsabadi, Ahmad Arabi; Sharifian Gh., Mohammad; Rahimpour, Ahmad; Soroush, Masoud
Abstract: Silver‐based nanomaterials have attracted considerable attention due to their antimicrobial activities. In this work, a silver (Ag)‐based metal organic framework (Ag‐MOF) is embellished with graphene‐oxide (GO), leading to the fabrication of a novel Ag‐based nanocomposite (GO‐Ag‐MOF) whose biocidal activity is higher than those of Ag‐MOF and GO nanomaterials. The nanocomposite is characterized using X‐ray photoelectron spectroscopy, transmission electron microscopy, scanning electron microscope, Fourier transform infrared spectra, ultraviolet−visible absorption spectra, X‐ray powder diffraction, dynamic light scattering, and nitrogen gas adsorption/desorption. The characterization shows that the Ag‐MOF nanoparticles are uniformly dispersed on the GO nanosheets surfaces without any agglomeration. Toxicities of GO‐Ag‐MOF, Ag‐MOF, and GO are assessed against the Gram‐negative bacteria, Escherichia coli and the Gram‐positive bacteria, Bacillus subtilis using the growth curve, fluorescence imaging, and flow cytometry methods. GO‐Ag‐MOF shows an outstanding antibacterial activity (higher than those of the Ag‐MOF and GO alone). The interaction of GO‐Ag‐MOF and Ag‐MOF with the bacteria leads to the extirpation of 95 and 85% of live bacteria cells, respectively. This study indicates that GO‐Ag‐MOF is a promising antibacterial nanocomposite, especially for biomedical applications. Abstract : Silver‐based nanomaterials and graphene oxide (GO) have shown potent antibacterial properties against bacteria. In this work, a silver‐based metal organic framework (Ag‐MOF) is decorated with GO. The growth curve, fluorescence spectroscopy, and flow cytometry methods point to a higher toxicity of the GO‐Ag‐MOF than those of Ag‐MOF and GO against Escherichia coli and Bacillus subtilis .